Peranan Pendidikan Agama Islam (Pai) Di Perguruan Tinggi Melalui Pendekatan Fenomenologis - Abdul Rohim (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2016)
This review will discuss the position and relevance of Islamic religious education at the Public University (PTU), which will explain the development of character-oriented PAI development with several studies, namely philosophical foundations and character education theories, positions and outlook on education Islamic religion in universities and the advantages and functions of Islamic education in higher education. The preparation is intended as knowledge in the development of Islamic Religious Studies course in college. It also aims to increase the intellectual treasury, about the role of Islamic religious education in college.